Recent Advances in Biomedical Photonic Sensors: A Focus on Optical-Fibre-Based Sensing - Mario Ochoa; José Francisco Algorri; Pablo Roldán-Varona; Luis Rodríguez-Cobo; José Miguel López-Higuera (Sensors, 2021)
In this invited review, we provide an overview of the recent advances in biomedical photonic sensors within the last five years. This review is focused on works using optical-fibre technology, employing diverse optical fibres, sensing techniques, and configurations applied in several medical fields. We identified technical innovations and advancements with increased implementations of optical-fibre sensors, multiparameter sensors, and control systems in real applications. Examples of outstanding optical-fibre sensor performances for physical and biochemical parameters are covered, including diverse sensing strategies and fibre-optical probes for integration into medical instruments such as catheters, needles, or endoscopes.